Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300384
|View full text |Cite
|
Sign up to set email alerts
|

Multi-plié

Abstract: We present the design concept of an accordion-fold interactive display to address the limits of touch-based interaction in airliner cockpits. Based on an analysis of pilot activity, tangible design principles for this design concept are identified. Two resulting functional prototypes are explored during participatory workshops with pilots, using activity scenarios. This exploration validated the design concept by revealing its ability to match pilot responsibilities in terms of safety, efficiency and collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…By combining tangible and touch features, interfaces can counteract the negative effects of turbulence by offering appropriate solutions [35,62,63]. Hutchins [35] presented a graphical interface for autopilot mode management systems.…”
Section: Touch the First Dimension Relates Tomentioning
confidence: 99%
See 1 more Smart Citation
“…By combining tangible and touch features, interfaces can counteract the negative effects of turbulence by offering appropriate solutions [35,62,63]. Hutchins [35] presented a graphical interface for autopilot mode management systems.…”
Section: Touch the First Dimension Relates Tomentioning
confidence: 99%
“…The results of their user study demonstrated that GazeForm generated a lower subjective mental workload and led to a higher efficiency of execution. In another study, Pauchet et al [63] explored a foldable interactive surface with the goal to make touch interaction in the cockpit more efficient and reliable.…”
Section: Touch the First Dimension Relates Tomentioning
confidence: 99%
“…Future work should take into consideration the impact of macro-and micro-properties on the contexts of use as they arise, i.e. either existing contexts which could benefit from the implementation of modular UIs (e.g., the same way nonmodular shape-changing control devices are studied to replace bulky control interfaces [79,80]) or new usages uniquely enabled by modular shape-changing UIs.…”
Section: Limitationsmentioning
confidence: 99%
“…Both studies were performed on a vibrating platform and asked participants to manage alerts during the tasks. GazeForm [31] and Multi-Plié [32] are two interfaces combining touch and physical interaction. GazeForm is a classical touchscreen which turns into a physical interface (i.e., a rotary encoder emerges from the surface) when the user does not look at it anymore.…”
Section: Interaction In the Cockpitmentioning
confidence: 99%